1994
DOI: 10.1111/j.1600-0722.1994.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with salivary buffering capacity in young adults in Stockholm, Sweden

Abstract: The buffering capacity and flow rate of stimulated whole saliva were assessed in 150 persons, 20–24 yr of age. The associations were assessed between the buffer value and the flow rate, some dietary factors, tobacco habits, use of oral contraceptives, and some demographic variables. The results demonstrate that a low flow rate may predict a low buffer value but not a high value. Flow rate accounted for the largest part of the buffering variation but morning and afternoon saliva sampling, female gender, food co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 11 publications
7
21
1
4
Order By: Relevance
“…This is in agreement with Wikner and Soder [73] who found females had a lower SS buffer capacity. Fenoll-Palomares et al [28] also found no significant differences in pH, and higher bicarbonate concentration in men than women.…”
Section: Effect Of Age and Gender On Salivary Parameterssupporting
confidence: 93%
“…This is in agreement with Wikner and Soder [73] who found females had a lower SS buffer capacity. Fenoll-Palomares et al [28] also found no significant differences in pH, and higher bicarbonate concentration in men than women.…”
Section: Effect Of Age and Gender On Salivary Parameterssupporting
confidence: 93%
“…This is in contrast to results obtained in other studies. A low salivary secretion rate has been found to correlate to a low buffering capacity (Fure and Zickert, 1990;Wikner and Soder, 1994).…”
Section: )mentioning
confidence: 97%
“…It is also advisable to avoid sugars-containing food and drinks close to bedtime (within one hour), 44 as salivary flow is low and its buffering capacity is reduced at night. 45,46 A common eating pattern, however, is to eat little and often -a pattern sometimes referred to as 'grazing' . In this case, suggesting that patients should limit food consumption to three times a day may be totally unrealistic and impractical.…”
Section: Dietary Recommendations For the Prevention And Management Ofmentioning
confidence: 99%